First-Cycle Simulation for Li-Rich Layered Oxide Cathode Material xLi2MnO3⋅(1-x)LiMO2 (x = 0.4). Issue 11 (1st January 2018) - Benedek, Roy
Abstract : Lithium-rich layered oxides (LRLO) x Li2 MnO3 (1- x )Li M O2 continue to attract attention owing to their promise of high capacity and energy density as lithium-ion battery cathodes, despite the degradation of atomic structure and energy density (voltage fade) with cycling. First-principles DFT calculations for the model systems M = Co and M = Mn0.5 Ni0.5 provide insights into the atomic-scale transformations in the bulk during the first charge and discharge of LRLO. The simulations were performed with the VASP code at the GGA+ U level. Molecular dynamics simulations were conducted at T = 1000 K (charge) and 2000 K (discharge) to accelerate the dynamics. Considerable Co migration to the Li layer occurs during the first charge for the system with M = Co, but the Li M O2 component remains substantially intact for the system with M = Mn0.5 Ni0.5 . First-charge oxygen dimerization in the M = Co system occurs in both the Li M O2 and the Li2 MnO3 components of the material, and exceeds than for M = Mn0.5 Ni0.5, where dimerization is essentially confined to the Li2 MnO3 component. About half of the oxygen dimers created during the voltage plateau dissociate during the first discharge. Analysis of the redox suggests that some Mn 3+ is generated during the first charge for the system M = Co.